Pengaruh Holding Time Annealing terhadap Perubahan Mikrostruktur Baja Struktur S690QL dan S235JR - Ari Wibowo; Hanifah Widiastuti; Nurul Laili Arifin; Nugroho Pratomo Aryanto (Politeknik Negeri Batam, 2021)
The S690 and S235JR structural steels are widely used in heavy equipment for the main frame structure. In general, the fabrication processes of heavy equipment involve welding processes that could change the mechanical properties of the materials. Therefore, in the fabrication process involving those steels, a heat treatment process is carried out after welding to modify the mechanical properties. The heat treatment process is conducted mainly to eliminate residual stresses and to reduce brittleness through the annealing process. In this study, annealing was carried out on the two steels to observe the effect of the heat treatment process on the hardness and microstructure of the material. The annealing process was conducted at 760 oC, holding time varied at 2, 4, 6, 8 and 10 hours, and a cooling rate of 20 oC/hour. After the annealing process, observations with a metallurgical microscope were done to see the final microstructure, followed by testing material hardness using the Rockwell B method. The test results showed that the annealing holding time affected the phases and grain size as well as the hardness of the steel S690 and S235JR. The largest grain size is formed with a holding time of 10 hours while the lowest hardness is also obtained at a holding time of 10 hours. Annealing holding time also affects the phase change from fine bainite to ferrite with large grains on S690 and reduces the size of pearlite on S235JR. The test results also show that long holding time has the potential to cause a decarburization effect on steel.